GE_GERICHTE P/5629/2014 vom 7. Februar 2017 - GE Cour de justice (2017)
DIFFAMATION ; SURSIS À L'EXÉCUTION DE LA PEINE ; EXEMPTION DE PEINE ; ACQUITTEMENT ; BONNE FOI SUBJECTIVE | CP.173.1 CP.34 CPP.433 CPP.422 CPP.135